FOXO acts as a positive regulator of CncC and deltamethrin tolerance in the red flour beetle, Tribolium castaneum. Issue 5 (9th February 2022) - Xu, Xin; Zhang, Nan; Meng, Xiangkun; Jiang, Heng; Ge, Huichen; Zheng, Yang; Qian, Kun; Wang, Jianjun
Abstract: BACKGROUND: Both forkhead box O (FOXO) and nuclear factor erythroid‐derived 2‐like‐2 (Nrf2) are key transcription factors related to stress responses. Whereas limited studies in mammals and Caenorhabditis elegans have revealed the interaction between FoxO/DAF‐16 and Nrf2/SKN‐1, the role of FOXO in metabolic detoxification and regulation of the Nrf2–Keap1 signaling pathway are poorly understood in insects. RESULTS: Using Tribolium castaneum as a model organism, we found that RNA interference‐mediated knockdown of FOXO enhanced deltamethrin‐induced lethality by affecting the messenger RNA (mRNA) levels of CYP6BQ cluster genes. We further demonstrated that injection of dsFOXO into the beetle larvae decreased expression of CncC and KEAP1 at both the mRNA and protein level. Notably, dual‐luciferase and electrophoretic mobility shift assays both confirmed direct regulation of CncC by FOXO, whereas Keap1 was directly regulated by CncC . CONCLUSION: FOXO can directly regulate the expression of CncC and indirectly regulate the expression of Keap1 through CncC . The data provide insights into the regulatory mechanisms of the Nrf2–Keap1 signaling pathway in insects. Abstract : The transcription factor FOXO is involved in deltamethrin tolerance of Tribolium castaneum by regulating expression of CYP6BQ genes through transcription factor CncC, and CncC directly regulates the repressor protein Keap1 by controlling its transcription. © 2022 Society of Chemical Industry.